Pelayanan Administrasi Terpadu Di Kecamatan Pasangkayu Kabupaten Pasangkayu - Susriani Susriani; Suasa Suasa; Nawawi Natsir (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to determine Integrated Administrative Services in Pasangkayu District, Pasangkayu Regency, which is studied based on the work motivation theory model according to Parasuraman (1988: 69). Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Guarantee), Empathy (Empathy), Tangible (Direct evidence), The type of research used is qualitative descriptive with purposive selection of informants and the number of informants selected is 5 people using data collection techniques, 1). Observation, 2). Interview, 3) Documentation. By analyzing all the interview results. Results of Research on Integrated Administrative Services in Pasangkayu District, Pasangkayu Regency, Based on the results of the discussion using 5 (Five) Service Quality indicators for integrated administrative services at the Pasangkayu District Office, Pasangkayu Regency, the author can draw the conclusion that the results of the research conducted by the author in the Pasangkayu District Office, Pasangkayu Regency through observation and the results of direct interviews with several informants, from five dimensions/aspects of assessment of Reliability, Responsiveness, Assurance, Empathy, Tangible (direct evidence). The author concludes that the implementation of government public services in the Pasangkayu District office, Pasangkayu Regency, is measured from the five indicators, which are assessed as indicators/dimensions of Reliability,Responsiveness,Empathy,Tangible (Direct Evidence), whereas in Assurance indicators/dimensions whose results are still not working well